Rút gọn các biểu thức sau:
\(A=\left(\dfrac{1}{\sqrt{a}+2}+\dfrac{1}{\sqrt{a}-2}\right):\dfrac{\sqrt{a}}{a-4}\)
\(B=\left(\dfrac{4x}{\sqrt{x}-1}-\dfrac{\sqrt{x}-2}{x-3\sqrt{x}+2}\right).\dfrac{\sqrt{x}-1}{x^2}\)
\(C=\left(\dfrac{1}{\sqrt{x}+3}+\dfrac{2\sqrt{x}}{x-9}\right).\dfrac{2\sqrt{x}+6}{\sqrt{x}-1}\)
\(D=\left(\dfrac{5\sqrt{x}-6}{x-9}-\dfrac{2}{\sqrt{x}+3}\right):\left(1+\dfrac{6}{x-9}\right)\)
\(E=\left(\dfrac{\sqrt{x}}{3+\sqrt{x}}+\dfrac{9+x}{9-x}\right).\left(3\sqrt{x}-x\right)\)
\(A=\left(\frac{1}{\sqrt{a}+2}+\frac{1}{\sqrt{a}-2}\right):\frac{\sqrt{a}}{a-4}\)\(ĐKXĐ:x\ge0;x\ne4\)
\(A=\frac{\sqrt{a}-2+\sqrt{a}+2}{\left(\sqrt{a}+2\right).\left(\sqrt{a}-2\right)}.\frac{a-4}{\sqrt{a}}\)
\(A=\frac{2\sqrt{a}}{a-4}.\frac{a-4}{\sqrt{a}}\)
\(A=2\)
\(B=\left(\frac{4x}{\sqrt{x}-1}-\frac{\sqrt{x}-2}{x-3\sqrt{x}+2}\right).\frac{\sqrt{x}+1}{x^2}\) \(ĐKXĐ:x\ne1,x>0\)
\(B=\left(\frac{4x.\left(\sqrt{x}-2\right)-\sqrt{x}+2}{\left(\sqrt{x}-1\right).\left(\sqrt{x}-2\right)}\right).\frac{\sqrt{x}-1}{x^2}\)
\(B=\frac{\left(\sqrt{x}-2\right).\left(4x-1\right)}{\left(\sqrt{x}-2\right)}.\frac{1}{x^2}\)
\(B=\frac{4x-1}{1}.\frac{1}{x^2}\)
\(B=\frac{4x-1}{x^2}\)
Vậy.....